The Effects of Excessive Aerobic Continuous and Interval Training Programs on Plasma Lipoproteins and Serum CRP in Women - A.A Gaeini; F Kazemi; A Behzare (Journal of Kerman University of Medical Sciences, 2012)
Background & Aims: Blood inflammatory factors have been recognized as major risk factors of cardiovascular diseases. The purpose of this study was to compare the efficacy of two methods of excessive aerobic continuous and interval training on plasma lipoproteins (TC, TG, LDL, HDL, VLDL) and serum CRP in women. Methods: A total of 20 women aged 35-45 years were randomly divided into the two groups of aerobic continuous and interval training. Subjects participated in an 8- week either aerobic continuous or interval running program (3 day / week, at 65-75% HRmax). Twenty four hours before the first training program and 24 hours after the final training session blood samples were collected in a fasted state. Results: No significant difference was found between the two groups in regard to TC, TG, LDL, HDL, VLDL and CRP levels in both pre- and post- tests. Aerobic continuous training induced significant decrease in TC, LDL, CRP and increase in HDL. Aerobic interval training induced significant decrease in TC, TG, LDL, CRP and increase in HDL too, but no significant difference was found between the two methods of training on plasma lipoproteins and serum CRP. Conclusion: Excessive aerobic continuous and interval training can have similar effects on plasma lipoproteins and serum CRP in women.